2015
DOI: 10.1016/j.virol.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Different DNA methylation pattern of HPV16, HPV18 and HPV51 genomes in asymptomatic HPV infection as compared to cervical neoplasia

Abstract: Epigenetic alterations of human papillomavirus (HPV) genome play an important role in virus life cycle and carcinogenic progression. The aim of the current study was to investigate the correlation between the grade of cervical pathology and DNA methylation status within the L1 gene and the long control region (LCR) of HPV16, HPV18 and HPV51. HPV genomes were analyzed using bisulfite DNA modification procedure with the subsequent amplification of target DNA regions and sequencing. A collection of 202 cervical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…Moreover, they showed that the viral URR becomes hypo-methylated upon squamous cell differentiation in cells capable of replicating the viral genomes and producing progeny viral particles. These data were corroborated by further studies showing that in cells capable of producing papillomavirus particles, the URR tends to become hypomethylated in more differentiated cells [6]. However, the E2BSs and in particular the SP1 binding site seem to be highly methylated in the very superficial cell layers consistent with the downregulation of the early genes and the activation of the late genes due to the SP1 site methylation in these fully differentiated cells (early late shift) [7].…”
Section: Dna Methylation Of Viral Genomes In the Pv Life Cyclementioning
confidence: 59%
“…Moreover, they showed that the viral URR becomes hypo-methylated upon squamous cell differentiation in cells capable of replicating the viral genomes and producing progeny viral particles. These data were corroborated by further studies showing that in cells capable of producing papillomavirus particles, the URR tends to become hypomethylated in more differentiated cells [6]. However, the E2BSs and in particular the SP1 binding site seem to be highly methylated in the very superficial cell layers consistent with the downregulation of the early genes and the activation of the late genes due to the SP1 site methylation in these fully differentiated cells (early late shift) [7].…”
Section: Dna Methylation Of Viral Genomes In the Pv Life Cyclementioning
confidence: 59%
“…The literature search yielded 572 potentially eligible studies; 44 studies [6], [7], [8], [9],[21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60] and 8819 women were included in the analysis (supplementary table 1, supplementary figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The L1 and L2 regions of other types of HPVs are methylated in cervical cancer/CIN. Aberrant methylation of CpG sites in the L1 and L2 regions of HPV18 and other high-risk HPV types including HPV31, HPV33, HPV45, HPV52, HPV51, and HPV58 relates with the progression from early-stage CINs and may be considered as a biomarker of the progression of cervical neoplasia [ 57 , 58 ]. Another research shows that the methylation of L1 in HPV16, HPV18, and HPV52 does not only play an important role in cervical cancer alone.…”
Section: Dna Methylation In Cervical Cancer and Cinmentioning
confidence: 99%